Understanding the emergence of 'Communitization' under India's National Rural Health Mission (NRHM): Findings from two Witness Seminars - Misimi Kakoti; Siddharth Srivastava; Prabir Chatterjee; Shraddha Mishra; Devaki Nambiar (Taylor & Francis Group, 2024)
ABSTRACTIndia's experience with the National Rural Health Mission (NRHM) is notable on account of nationally formalising - at scale - community action in service delivery, monitoring, and planning of health services. A study was undertaken to document and create a historical record of NRHM's 'communitization' processes. The oral history method of the Witness Seminar was adopted and two virtual seminars with five and nine participants, respectively, were conducted, and supplemented with 4 in depth interviews. Analysis of transcripts was done using ATLAS.ti 22 with the broad themes of emergence, evolution, and evaluation and impact of 'communitization' under NRHM. This paper engages with the theme of 'emergence' and adopts the Multiple Streams Framework (MSF) conceptualised by John Kingdon for analysis. Key findings include the pioneering role of boundary spanning decision makers and the Jan Swasthya Abhiyan (JSA) in advocacy and design of 'communitization' structures, and the legacy of rights based social mobilizations and state-civil society partnerships in health during the 1990s influencing the ethos underlying 'communitization'. Democracy, leadership from the civil society in policy design and implementation, and state-civil society partnerships are linked to the positive results witnessed as part of 'communitization' in NRHM.